Blood in their eyes : the Elaine Massacre of 1919 - Stockley, Grif (The University of Arkansas Press, 2020)
"The second edition of the authoritative text on the Elaine Massacre which took place in Elaine, Arkansas in 1919. With contributions by fellow historians Brian K. Mitchell and Guy Lancaster, this second edition of Blood in Their Eyes draws from recently discovered sources to explore in greater detail the actions of the mob and the lives of those who survived the massacre"--